The lack of wage growth and the falling NAIRU - Bell, David N.F.; Blanchflower, David G. (London, 2018)
"There remains a puzzle around the world over why wage growth is so benign given the unemployment rate has returned to pre-recession levels. It is our contention that a considerable part of the explanation is the rise in underemployment which rose in the Great Recession but has not returned to pre-recession levels even though the unemployment rate has. Involuntary part- time employment rose in every advanced country and remains elevated in many in 2018. In the UK we construct the Bell/Blanchflower underemployment index based on reports of whether workers, including full-timers and those who want to be part-time, who say they want to increase or decrease their hours at the going wage rate. If they want to change their hours they report by how many. Prior to 2008 our underemployment rate was below the unemployment rate. Over the period 2001-2017 we find little change in the number of hours of workers who want fewer hours, but a big rise in the numbers wanting more hours. Underemployment reduces wage pressure. We also provide evidence that the UK Phillips Curve has flattened and conclude that the UK NAIRU has shifted down. The underemployment rate likely would need to fall below 3%, compared to its current rate of 4.9% before wage growth is likely to reach pre-recession levels. The UK is a long way from full-employment."